CGR11 promotes hepatocellular carcinoma progression by regulating autophagy through the PI3K/AKT pathway - Zhou, Jia; Liu, Sulai; Song, Yinghui; Liu, Junjie; Tan, Zhiguo; Liu, Jie; Han, Xiaoxia; Xing, Yang; Wang, Xinrun; Peng, Chuang; Sun, Bo; Leng, Yufang (Frontiers in Cell and Developmental Biology, 2026)
BackgroundHepatocellular carcinoma (HCC), the predominant pathological subtype of primary liver cancer, remains a major global health burden with poorly defined molecular mechanisms. Cell growth regulator 11 (CGR11), a novel secreted protein characterized by EF-hand motifs, has recently emerged as a potential extracellular signaling modulator in tumor biology. Although implicated in cancer cell proliferation and metastasis, its precise role and regulatory mechanisms in HCC progression have not been elucidated.MethodsWe integrated bioinformatics analysis with single-cell transcriptomic profiling and CellChat-based intercellular communication mapping. CGR11 expression and localization were validated in tissue microarrays, HCC cell lines, and tumor specimens using immunohistochemical staining, qRT-PCR, and Western blotting. In vitro experiments and both subcutaneous and orthotopic xenograft models were established to evaluate the biological effects of CGR11 overexpression and knockdown. RNA sequencing, LC3 fluorescence assay, and transmission electron microscopy were conducted to elucidate the underlying molecular mechanism.ResultsCGR11 expression was markedly increased in HCC tissues relative to adjacent non-tumorous liver tissues and correlated with poor patient prognosis. Functional and mechanistic analyses demonstrated that CGR11 promotes HCC cell proliferation, invasion and tumor growth by inhibiting autophagy levels through activation of the PI3K/AKT signaling. Conversely, CGR11 knockdown restored autophagy and significantly suppressed tumor progression in both cellular and animal models.ConclusionOur findings establish CGR11 as a novel oncogenic regulator that contributes to HCC progression by suppressing autophagy via PI3K/AKT activation. Targeting the CGR11-PI3K/AKT axis may therefore provide a promising avenue for precision therapeutic intervention in HCC.